2017
DOI: 10.1007/s40262-017-0506-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal Drug Transporters and Drug Interactions

Abstract: Transporters in proximal renal tubules contribute to the disposition of numerous drugs. Furthermore, the molecular mechanisms of tubular secretion have been progressively elucidated during the past decades. Organic anions tend to be secreted by the transport proteins OAT1, OAT3 and OATP4C1 on the basolateral side of tubular cells, and multidrug resistance protein (MRP) 2, MRP4, OATP1A2 and breast cancer resistance protein (BCRP) on the apical side. Organic cations are secreted by organic cation transporter (OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(204 citation statements)
references
References 997 publications
3
177
0
4
Order By: Relevance
“…Consistent with previous in vitro findings, a clinical DDI study performed in healthy subjects with a substrate (i.e., digoxin) and an inhibitor of P‐gp (i.e., quinidine) showed that these drugs did not influence lenalidomide plasma levels (and vice versa) . Moreover, DDIs involving transporters at the renal level are usually of limited magnitude as shown recently in a comprehensive review . The DDI interaction observed in patients (between temsirolimus and lenalidomide) may arise from the fact that the role of P‐gp in MM patients might be altered by changes induced by the disease in the proximal tubules leading to clinically significant DDIs …”
Section: Immunomodulatory Drugssupporting
confidence: 80%
“…Consistent with previous in vitro findings, a clinical DDI study performed in healthy subjects with a substrate (i.e., digoxin) and an inhibitor of P‐gp (i.e., quinidine) showed that these drugs did not influence lenalidomide plasma levels (and vice versa) . Moreover, DDIs involving transporters at the renal level are usually of limited magnitude as shown recently in a comprehensive review . The DDI interaction observed in patients (between temsirolimus and lenalidomide) may arise from the fact that the role of P‐gp in MM patients might be altered by changes induced by the disease in the proximal tubules leading to clinically significant DDIs …”
Section: Immunomodulatory Drugssupporting
confidence: 80%
“…Increasing evidence has indicated that a drug transporter can be a site of significant DDIs where a ‘perpetrator’ drug can affect the clearance and the systemic exposure of a ‘victim’ drug, resulting in exaggerated/diminished therapeutic and/or side effects (39). Morphine is commonly co-administrated with other drugs which may serve as “perpetrator” agents via transporter inhibition and cause undesirable outcomes of morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane protein fractions were extracted from tissues as previously described (23). Briefly, renal tissue (300 mg) was homogenized in lysis buffer (0.1 M Tris-HCL (Sigma Aldrich), pH 7.5), containing 3 µL/mL protease inhibitor cocktail (Sigma Aldrich), and 50 µg/mL phenylmethylsulfonyl fluoride (Bioshop, Burlington, ON, Canada).…”
Section: Membrane Protein Extraction and Western Blot Analysismentioning
confidence: 99%